MiR-141-3p is Poorly Expressed in Polycystic Ovary Syndrome and Correlates with Glucose and Lipid Metabolism. (8th October 2021) - Fan, Lingye; Wang, Chunyan; Zhan, Ping; Liu, Yaofang
Abstract : Polycystic ovary syndrome (PCOS) is a common endocrinopathy with high prevalence. miR-141-3p downregulation was reported in PCOS rats. This study intended to investigate miR-141-3p expression in serum of PCOS patients and its correlation with glucose and lipid metabolism. A total of 100 PCOS patients and 100 healthy controls were enrolled in this study. Clinical parameters and glucose and lipid indexes were analyzed. A 3-month fat reduction intervention was conducted to PCOS-obese patients. Expressions of miR-141-3p and PTEN were detected. WHR and levels of TG, HDL-C, FBG, FINS, HOMA- β, and HOMA-IR showed significant differences in PCOS patients. miR-141-3p was downregulated in PCOS patients. Area under ROC curve of miR-141-3p diagnosing PCOS-obese patients was 0.985 with specificity 95.35% and flexibility 93.33%. Levels of glucose and lipid metabolism indexes were increased while HDL-C level was decreased in miR-141-3p low expression group. Indexes of PCOS-obese patients were improved and miR-141-3p was upregulated after fat reduction intervention. PTEN was upregulated in PCOS patients and negatively correlated with miR-141-3p. In conclusion, miR-141-3p was downregulated in PCOS patients and had higher diagnostic value on PCOS and associated with glucose and lipid metabolism. miR-141-3p might play a role in glucose and lipid metabolism in PCOS-obese patients by targeting PTEN.